The production of derivational bound morphemes in the poetry of Sherko Bekas - Mustafa, Parwin; Farhadi, Sajida (Humanities Journal of University of Zakho, 2022)
The current study entitled ‘The production of derivational bound morphemes in the poetry of Sherko Bekas’ seeks to demonstrate how to form new words and to identify the mechanisms of their production and formation in Sherko Bekas’ poetry by attaching derivational bound morphemes to the stems of the lexical vocabulary according to what is found in the morphological rules of the Kurdish Language. In other words, it identifies the process of producing new words in the poetry of Sherko Bekas based on familiar and its morphological system from the means of forming words. The study relied on the descriptive method and the statistical side in determining and extracting proportions. The study consists of an introduction and two main parts. The first part is concerned with the theoretical background by defining the concepts, the term morphological units, derivational affixes and stating their types, as well as defining the lexical unit and affirming two types (nominal and descriptive). The second one is devoted to the practical part which deals with the definition and the production of derivational bound morphemes in the poetry of Sherko Bekas. Furthermore, it includes accurate statistical analysis of the names and adjectives produced and formed in the poet’s poetry. The summary can be found in Arabic and English languages.